Possibilities and problems with identification and determination of "new" hypnotics - Ondra, Peter; Zedníková, Kateřina; Matlach, Radek (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
Authors discuss problems with identification and determination of flunitrazepam and zolpidem in biological material (BM). Over the recent years, these two structurally different substances have become the most frequently used as well as abused hypnotic drugs. This study presents applicability of immunochemical methods in the screening of flunitrazepam, one of the most commonly prescribed drugs among the benzodiazepines. Herein described techniques, a liquid-liquid (L-L) extraction, solid phase extraction (SPE) and the so-called "freeze out" method are used for isolation of the above mentioned compounds from BM. Besides the thin layer chromatography (TLC) and gas chromatography - mass spectrometry (GC-MS) applied in qualitative analysis, the study also describes a gas chromatography with electron capture detector (GC-ECD) and gas chromatography with nitrogen phosphorus detector (GC-NPD) optimized for the determination of flunitrazepam and zolpidem in blood (serum). Successful analyses of these two substances are of major importance, especially in interpreting the results of forensic toxicological examinations.
Keywords: Substance Abuse Detection; pyridiny; Flunitrazepam; lidé; chromatografie plynová; Pyridines; odhalování abúzu drog; Forensic Toxicology; Humans; soudní toxikologie; flunitrazepam; hypnotika a sedativa; Chromatography, Gas; Hypnotics and Sedatives